Entrepreneurial Leadership, Innovative Behavior, Organizational Effectiveness: A Mediation Analysis - Rumaji; Ilhami, Susanti Dwi (JOELS: Journal of Election and Leadership, 2024)
The concept of organizational effectiveness emphasizes leadership carried out by leaders. Therefore, it is important to know the factors that can increase organizational effectiveness. This research has an aim to examine (i) the effect of entrepreneurial leadership on organizational effectiveness;(ii) the effect of entrepreneurial leadership on innovative behavior; (iii) the effect of innovative behavior on organizational effectiveness; (iv) the role of innovative behavior as a mediation variable. 90 questionnaires were distributed namely online and offline to SMEs owners in Rembang Regency as a data collection research method by using likert scale. The researchers used this PLS-SEM analytical method because the number of samples used in the study was small. Four results of the study have found: (i) there is a positive and significant effect between entrepreneurial leadership and organizational effectiveness; (ii) there is a positive and significant effect between entrepreneurial leadership and innovative behavior; (iii) there is a positive and significant effect between innovative behavior and organizational effectiveness; (iv) innovative behavior could play the role as mediating variable in the relationship between entrepreneurial leadership and organizational effectiveness. The organizations that practice entrepreneurial leadership and innovative behavior have better performance. Because it is important for organizations, especially SMEs owners to carry out entrepreneurial leadership in running a business.